The influence of local and landscape factors on arthropod predator diversity in the Sundays River Valley, Eastern Cape, South Africa - Galloway, Alistair Duncan (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScConsEcol)--Stellenbosch University, 2019.